2017
DOI: 10.1088/1748-605x/aa5bbc
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun scaffolds functionalized with heparin and vascular endothelial growth factor increase the proliferation of endothelial progenitor cells

Abstract: In severe cases of peripheral arterial disease, tissue loss can occur and the use of vascular grafts can be necessary. However, currently, there are no suitable substitutes for application in small diameter vessels. The aim of this work has been to produce scaffolds with adequate properties for application as vascular substitutes. Polycaprolactone scaffolds were produced by the electrospinning technique. The surface of the scaffolds was functionalized with heparin and vascular endothelial growth factor (VEGF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…MSCs can be easily sampled, isolated, and largely amplified in vitro. Transplanted MSCs in vivo can secrete many vasoactive growth factors, including vascular endothelial growth factor, which is one of the main factors that promotes vascular growth [4]. MSCs can release cytokines to increase the number of EPCs in the peripheral blood circulation, which in turn promotes angiogenesis and the recovery of neurological function through angiogenesis.…”
Section: Dmentioning
confidence: 99%
“…MSCs can be easily sampled, isolated, and largely amplified in vitro. Transplanted MSCs in vivo can secrete many vasoactive growth factors, including vascular endothelial growth factor, which is one of the main factors that promotes vascular growth [4]. MSCs can release cytokines to increase the number of EPCs in the peripheral blood circulation, which in turn promotes angiogenesis and the recovery of neurological function through angiogenesis.…”
Section: Dmentioning
confidence: 99%
“…The first approach relies on the induction of vascularization by endothelial precursors using angiogenic factors such as VEGF. For instance, Braghirolli et al [ 84 ] demonstrated that an electrospun poly(caprolactone) scaffold loaded with VEGF promoted the penetration and proliferation of EPCs within the 3D matrix. This process is primarily EC regulated and, in the context of TE, specific interactions with the scaffold material and other cell types are needed for optimal in-vitro vascularization.…”
Section: In-vitro Modeling Of 3d Vascularized Bone Models Through Tismentioning
confidence: 99%
“…8,9 Smooth muscle cells when loses its contractile protein and quiescence state will undergo increased proliferation, migration and produce excessive extracellular matrix (ECM) proteins and pro-inammatory cytokines and growth factors which eventually lead to deadly vascular diseases. 8,10 Several research group have made attempts to modulate the phenotype of vascular smooth muscle cells through approaches such as micro-patterning, 9,11,12 electrospinning, [13][14][15] coating of heparin 8,16 or having endothelial cells (ECs) on the inner side of scaffold. 10,16,17 While micro-patterning creates a dened cellular monolayer of cells, it rapidly loses its regularity when translated into multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Several research group have made attempts to modulate the phenotype of vascular smooth muscle cells through approaches such as micro-patterning, 9,11,12 electrospinning, [13][14][15] coating of heparin 8,16 or having endothelial cells (ECs) on the inner side of scaffold. 10,16,17 While micro-patterning creates a dened cellular monolayer of cells, it rapidly loses its regularity when translated into multiple layers. 12,18 This 2D nature of micro-patterned cellular sheets presents a major limitation for tissue engineering, where the assembly of thick multi-component cell construct is desired.…”
Section: Introductionmentioning
confidence: 99%